STUDY AND DETERMINATION OF DISEASES AND PESTS OF REPAIR RASPBERRY «BRYANSKOE DIVO» IN THE SOUTH-EAST OF KAZAKHSTAN - Zhailibayeva Lyazzat Asylbekovna,; Oleichenko Sergey Nikolaevich,; Esenalieva Maira Danataevna,; Ismail Demirtas, (Scientific Journal of Pedagogy and Economics, 2020)
The intensity of diseases and pests was determined in LLP "Kazakh Research Institute of Plant Protection and Quarantine named after Zhazken Zhiembayev" in the test center of phytosanitary laboratory analysis for phytopathological and entomological examination. As a result of the analysis of entomological examination on the leaves of raspberries were found pests of the plant. No pests or nematodes were found in soil samples. On the basis of the symptoms of the disease and phytopathological analyses, it was found that the presented samples of raspberries are parasitic with purple spot, the causative agent of Didymella applanala, as well as secondarily inhabited by fungi of the genera Fuzarium, Aspergillius, Alternaria, Penicillium, Mucor. Classical phytopathological methods were used for the phytopathological diagnosis of raspberry disease. Determination of fungal and bacterial microflora was carried out on morphological and cultural characteristics of the colony of fungi and bacteria isolated in pure culture.